Absorption, Mentalizing, and Mysticism: Sensing the Presence of the Divine. (29th May 2019) - Coleman III, Thomas; Bartlett, James; Holcombe, Jenny; Atkinson, Andrew; Swanson, Sally; Silver, Christopher; Hood Jr., Ralph
Abstract : Research suggests trait absorption, individual differences in Theory of Mind (ToM), and orthopraxical training are important for explaining a variety of extraordinary experiences typically associated with religion. However, no studies exist quantifying ToM ability or testing its relationship with trait absorption in the prediction of what is arguably the most ubiquitous type of extraordinary experience—the mystical experience. To address this, two exploratory studies were conducted using a sample of meditators (N = 269) and undergraduate students (N = 123). In study one, regression analyses revealed weekly religious/spiritual practice, absorption, and mentalizing predict increased mystical experiences. Moreover, moderation analysis indicated the absorption-mysticism relationship is stronger among individuals with lower mentalizing ability. Study two only replicated the relationship of absorption and weekly practice with mysticism. These studies highlight the robust contribution of absorption in mystical experiences and suggest a more dynamic role for mentalizing than is accounted for in the current literature.